Negotiating Identity of Muslim Women in Bajawa Cafe: Gender and Islamic Perspective - Sunandar, Crystalina Malika; Mahbuby, Dwiki Arif Nabil; Saputra, Nur Hidayat Hadi; Arief, Nazil Muchammad (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2024)
This research investigates how Muslim women perform at Bajawa Cafe, influenced by the construction of Islamic teachings and gender roles. The study aims to illustrate how Muslim women are shaped by societal production and regulation, employing qualitative methods through ethnographic and netnographic approaches. It examines the interplay of Islamic teachings and gender norms to analyze the construction of Muslim women's identities within the context of Bajawa Cafe. Data was collected through observations of Hijabi Muslim women's performances at Bajawa Cafe in Kemang, in-depth interviews, data visualizations, and social media analysis. The findings reveal that these women, through activities such as halal parties, challenge the traditional Islamic teachings and gender expectations imposed on them. Bajawa Cafe serves as a space where they navigate and negotiate these societal constructs. The results suggest that Muslim women at Bajawa Cafe resist the societal and religious constraints shaped by Islamic teachings and gender roles. Their performances reflect an ongoing process of negotiation, demonstrating agency in redefining their identities. In conclusion, Bajawa Cafe has emerged as a significant space for Muslim women to express and reconcile their interpretations of Islamic teachings and gender norms.